Seasonal reproduction and gonadal function: a focus on humans starting from animal studies. Issue 1 (29th October 2021) - Beltran-Frutos, Ester; Casarini, Livio; Santi, Daniele; Brigante, Giulia
Abstract: Photoperiod impacts reproduction in many species of mammals. Mating occurs at specific seasons to achieve reproductive advantages, such as optimization of offspring survival. Light is the main regulator of these changes during the photoperiod. Seasonally breeding mammals detect and transduce light signals through extraocular photoreceptor, regulating downstream melatonin-dependent peripheral circadian events. In rodents, hormonal reduction and gonadal atrophy occur quickly and consensually with short-day periods. It remains unclear whether photoperiod influences human reproduction. Seasonal fluctuations of sex hormones have been described in humans, although they seem to not imply adaptative seasonal pattern in human gonads. This review discusses current knowledge about seasonal changes in the gonadal function of vertebrates, including humans. The photoperiod-dependent regulation of hypothalamic–pituitary–gonadal axis, as well as morphological and functional changes of the gonads is evaluated herein. Endocrine and morphological variations of reproductive functions, in response to photoperiod, are of interest as they may reflect the nature of past population selection for adaptative mechanisms that occurred during evolution.